Seasonal and interannual changes in water temperature affect the genetic structure of a Daphnia assemblage ( D. longispina complex) through genotype‐specific thermal tolerances - Rüdiger J. Paul; Ansgar Mertenskötter; Olaf Pinkhaus; Ralph Pirow; Ulrike Gigengack; Ina Buchen; Marita Koch; Wolfgang Horn; Bettina Zeis (Limnology and Oceanography, 2012)
A field and laboratory study was carried out over 3 yr to determine relationships between seasonal and interannual changes in temperature (year‐specific temperature courses, presence or absence of ice in winter) and the genetic structure (composition of multilocus genotypes [MLGs]) of a Daphnia longispina assemblage. Field studies on temperature and genetic structures were linked with laboratory analyses to evaluate the thermal tolerance of long‐term 12°C‐, 18°C‐, and 24°C‐acclimated clonal lineages (CLs) derived from abundant MLGs sampled in the field (surface water and thermocline). The tolerance to warm temperatures (heat tolerance) was lowest in CLs derived from MLGs that were dominant directly after or before winter (winter‐CLs), higher in “spring‐autumn‐CLs,” and highest in “summer‐CLs.” Winter‐CLs also showed the highest degree of physiological plasticity. The differences in heat tolerance were mainly related to the different genotypes of the phosphoglucomutase ( PGM ) locus. Temperature conditions during winter and early spring affected the heat tolerance of all CLs as well as the success of different winter survival strategies (overwintering, resting eggs). Heat tolerance was lowest in CLs derived from MLGs sampled in 2006 (after the coldest winter and spring period), higher in CLs from 2005 (after a less cold winter and spring period), and highest in CLs from 2007 (after a warm, ice‐free winter). In addition to other environmental factors (predation, parasitism, food), seasonal and interannual changes in temperature affect Daphnia genetic structure through genetic differences in thermal responses, thermal tolerance, and physiological plasticity.

Cationic composition and acid–base state of the extracellular fluid, and specific buffer value of hemoglobin from the branchiopod crustacean Triops cancriformis - Ralph Pirow; Ina Buchen; Marc Richter; Carsten Allmer; Frank Nunes; Andreas Günsel; Wiebke Heikens; Tobias Lamkemeyer; Björn M. von Reumont; Stefan K. Hetz (Journal of Comparative Physiology B, 2009)